Beyond Product Attributes: The Role of Segmentation, Targeting, Positioning in Shaping Consumer Satisfaction in the Agri-Food Sector in Kediri Regency, Indonesia - Wahyudi, Agus; Abu Talkah; Deby Santyo Rusandy (HM Publisher, 2024)
The agri-food sector in Kediri Regency, Indonesia, is undergoing a transformative phase, marked by the dynamic interplay of traditional agricultural practices and the evolving demands of the modern market. While product attributes such as quality and price remain pivotal in consumer decision-making, the strategic utilization of segmentation, targeting, and positioning (STP) has emerged as a critical determinant of consumer satisfaction. This research delves into the profound impact of STP on consumer satisfaction within the agri-food sector of Kediri Regency, aiming to provide actionable insights for businesses navigating this competitive landscape. The study employed a quantitative methodology, involving the collection of data from 60 consumers through structured questionnaires. The survey instrument encompassed questions designed to gauge consumer perceptions of segmentation, targeting, positioning, and their overall satisfaction with agri-food products. The data analysis was conducted using statistical software, employing descriptive statistics to elucidate respondent demographics and their perspectives on STP and satisfaction. Furthermore, multiple regression analysis was leveraged to rigorously test the research hypotheses and illuminate the intricate relationship between STP and consumer satisfaction. The empirical findings of this research underscore the positive and significant influence of STP on consumer satisfaction within the agri-food sector of Kediri Regency. The results unequivocally demonstrate that effective segmentation, targeting, and positioning strategies empower agri-food businesses to cultivate stronger consumer relationships and achieve sustainable growth in an increasingly competitive market. The study concludes that STP is an indispensable tool for agri-food businesses in Kediri Regency to enhance their marketing prowess and foster enduring consumer loyalty. By meticulously tailoring their offerings to specific consumer segments, businesses can elevate consumer satisfaction and fortify their market position.